Reticulin antibodies in patients with coeliac disease and their relatives. Issue 8 (August 1975) - Stevens, F M; Lloyd, R; Egan-Mitchell, B; Mylotte, M J; Fottrell, P F; Wright, R; McNicholl, B; McCarthy, C F
Abstract : The sera of 69 index coeliac patients, 121 of their first-degree relatives, and 104 controls were screened for the presence of reticulin antibodies. Among the untreated coeliac patients 75% of adults and 93% of children had reticulin antibody in their serum. Reticulin antibody was not present in any adequately treated coeliac patient. Of the first-degree relatives, 21 were reticulin antibody positive; 17 of these were biopsied and 12 were shown to have coeliac disease. Sixty-five of the coeliac relatives who did not have reticulin antibodies in their sera were biopsied and two had coeliac disease. Of the 68 relatives and 63 controls with normal biopsies, five of the relatives and four of the controls were reticulin antibody positive.